The Notion of Evolution and its Understanding by Pupils of Secondary Schools (ISCED 2 a 3) - Müllerová, Lucie (Scientia in educatione, 2020)
The research deals with the evolution of organisms. It focuses on current knowledge and opinions of pupils from lower and upper secondary schools. The aim is to determine whether pupils are able to realize the importance of biological notions from the perspective of evolutionary processes. First, seven hypotheses are presented, which concern the adaptation of organisms, evolution of organisms, intraspecific competition, speciation, Darwinism and Neo-Darwinism. In total 586 pupils from 8 schools were given a questionnaire. It was found out that in the context of evolutionary processes the pupils have problems to understand commonly known biological or evolutionary notions (e.g., adaptation). On the other hand, some pupils can easily define some more complicated evolutionary topics such as Neo-Darwinism.